Comparison of Light Transmission Aggregometry and VerifyNow in Detecting Clopidogrel Resistance and Factors Affecting Clopidogrel Resistance in AMI-EST Patients Undergoing Percutaneous Coronary Intervention: A Cross-Sectional Study - Astuti Giantini; Ina Susianti Timan; Erlin Listiyaningsih; Rahajuningsih Dharma; Rianto Setiabudy; Idrus Alwi; Lia Gardenia Partakusuma; Nuri Dyah Indrasari; Alida Roswita Harahap; Siskawati Suparmin; Windy Sahar; Renan Sukmawan (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Light transmission aggregometry (LTA) and VerifyNow is commonly used to measure platelet responsiveness to clopidogrel. This study aimed to compare the results of LTA and VerifyNow P2Y12 assay for assessing the clopidogrel resistance in patients undergoing percutaneous coronary intervention and determine factors affecting clopidogrel resistance.METHODS: The subjects were 119 patients who underwent percutaneous coronary intervention (PCI) and had given loading dose of 600 mg clopidogrel. Blood samples were taken at 6 hour after clopidogrel loading dose. Platelet aggregation was measured by LTA and VerifyNow.RESULTS: LTA and VerifyNow assay showed fair agreement with Kappa=0.270, p=0.001. The proportion of resistance to clopidogrel using VerifyNow was 21.8% and LTA was 47.1%. Patients with diabetes melitus were more likely to develop clopidogrel resistance than patients without diabetes (OR of 7.67; 95% CI: 1.87-31.50; p=0.005).CONCLUSION: The ability of LTA and VerifyNow in detecting clopidogrel resistance were not comparable. Multivariate analysis results for VerifyNow shows diabetes mellitus as the greatest predictors of clopidogrel resistance.KEYWORDS: agreement, clopidogrel resistance, LTA, predictor, VerifyNow